MODEL ARSITEKTUR POHON DI ARBORETUM FAKULTAS KEHUTANAN UNIVERSITAS LAMBUNG MANGKURAT - Muhammad Febri Hamdani; Basir Achmad; Setia Budi Peran (Universitas Lambung Mangkurat, 2022)
The research on the Arboretum Tree Architecture Model aims to analyze the types, functions and forms of architectural models that grow in the Arboretum of the Faculty of Forestry, Lambung Mangkurat University. The method used in this study was a descriptive analysis method of the architectural model. Based on the results of the analysis at the Arboretum of the Faculty of Forestry found 6 models of tree architecture from tree species with a diameter of 20 cm. The architectural forms/models of trees in the Arboretum were Aubreville with the type of ketapang (Terminalia catappa), Corner with the type of Palm Raja (Rostonea regia), Prevost with the type of Pulai (Alstonia scholaris), Raux with the type of Glodokan Tiang (Polyalthia longifolia), Troll with the type of Acacia mangium (Accacia mangium), and Cape (Mimusops elengi). It is suggested that the Arboretum of the Faculty of Forestry needs to add local tree species, especially those in Kalimantan while at the same time adding local tree architecture types so as to increase the knowledge of students or any parties who need it.Penelitian tentang Model Arsitektur Pohon Arboretum bertujuan untuk menganalisis jenis-jenis, fungsi dan bentuk model arsitektur yang tumbuh di Arboretum Fakultas Kehutanan Universitas Lambung Mangkurat. Metode yang digunakan dalam penelitian ini adalah metode analisis deskriptif terhadap model arsitektur. Berdasarkan hasil analisis di Arboretum Fakultas Kehutanan ditemukan 6 model arsitektur pohon dari beberapa jenis pohon yang berdiamater ≥ 20 cm. Pohon di Arboretum memiliki Bentuk/model arsitektur yaitu Aubreville dengan jenis ketapang (Terminalia catappa), Corner dengan jenis Palem Raja (Rostonea regia), Prevost dengan jenis Pulai (Alstonia scholaris), Raux dengan jenis Glodokan Tiang (Polyalthia longifolia), Troll dengan jenis Akasia Mangium (Accacia mangium), dan Tanjung (Mimusops elengi). Disarankan bahwa di Arboretum Fakultas Kehutanan perlu adanya penambahan jenis-jenis pohon lokal, khususnya yang ada di Kalimantan sekaligus menambah type arsitektur pohon local sehingga lebih menambah ilmu pengetahuan para mahasiswa atau pihak mana saja yang memerlukannya